2018
DOI: 10.2147/jmdh.s156264
|View full text |Cite
|
Sign up to set email alerts
|

The association of sociodemographic characteristics and sexual risk behaviors with health literacy toward behaviors for preventing unintended pregnancy among university students

Abstract: PurposeThe aim of this study was to determine whether there is an associated effect between sociodemographic characteristics and sexual risk behaviors with health literacy in preventing unintended pregnancy among university students in Chon Buri province, Thailand.Participants and methodsA cross-sectional study design was used. The data were collected between February and May, 2017. A self-administered questionnaire was developed by the Ministry of Public Health and supported by the evolving concept of health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…[ 5 13 14 15 16 17 ] Nevertheless, HLSU may influence the substance abuse, but there is no other study related among adolescent and there are no statistics and evidence available on this subject in Thailand. [ 18 19 ] Thus, investigating the effect of HLSU on substance abuse may help reduce the risk of their substance abuse behaviors and provide guidance for developing the substance abuse prevention interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 13 14 15 16 17 ] Nevertheless, HLSU may influence the substance abuse, but there is no other study related among adolescent and there are no statistics and evidence available on this subject in Thailand. [ 18 19 ] Thus, investigating the effect of HLSU on substance abuse may help reduce the risk of their substance abuse behaviors and provide guidance for developing the substance abuse prevention interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy has been reported as the main behavioral factor in preventing unwanted pregnancy [40]. According to Thongnopakun et al [43], college students with low health literacy were more likely to engage in inappropriate pregnancy-prevention behaviors. Health literacy is the main behavioral factor when it comes to preventing unintended pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is also effected by factors such as education, ethnicity, gender, age, profession, income, culture, language, and social support. 15 , 16 However, this study focused on several variables including age, grade point average, average allowance, parent's marital status, and living with parents that also indirectly affected the sexual and reproductive health of the respondents. This can be assumed that students who are performing well in school may have higher knowledge and understanding toward sexual health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the health education study which found that the mean scores of health literacy were higher than those in the observation group after receiving the Sex Must Safe Program, the health education program, which included all the elements of health literacy. 16 …”
Section: Discussionmentioning
confidence: 99%